The relationship between organizational commitment and job satisfaction among executive and non-executive employees at public works department, Kota Samarahan, Sarawak/ Muhamad Arifin Mat Zahari - Mat Zahari, Muhamad Arifin (2016)
This study examined the relationship between organizational commitment and job satisfaction. The research carried out among employees at Public Works Department, Kota Samarahan, Sarawak. The main purpose of this study is to identify the three component of organizational commitment (affective commitment, continuance commitment and normative commitment) and job satisfaction among executive and non-executive employees at Public Works Department, Kota Samarahan, Sarawak. This study used a questionnaire to obtain the data before running in SPSS version 20.0. The results showed that affective commitment and normative commitment are having positive relationship with job satisfaction while continuance commitment have a negative relationship with job satisfaction among executive and non executive employees at Public Works Department, Kota Samarahan, Sarawak.